Pengembangan Aplikasi E-Learning Gamifikasi untuk Pembelajaran Matematika di SMPN 4 Curug - Muhammad Rafi Fauzan Hastiar; Mahmudin Mahmudin; Imam Halim Mursyidin (Universitas Islam Syekh Yusuf Tangerang, 2026)
In the midst of a rapidly evolving digital era, e-learning has emerged as a flexible and accessible learning solution. However, its implementation still faces challenges in sustaining student motivation and participation, particularly in mathematics, which demands deep conceptual understanding. Unlike previous studies that were predominantly web-based or lacked gamification, this research develops a gamified e-learning application on the Android platform, focusing on enhancing mathematics learning motivation through features such as leaderboards, interactive quizzes, and a point system. The application was designed using the Extreme Programming (XP) method, integrated with the Hygraph backend, and tested at SMPN 4 Curug, Tangerang Regency, involving eighth-grade students. A total of 71 participants (students and teachers) were involved in the evaluation using User Acceptance Testing (UAT), which resulted in an acceptance rate of 80.7%. These findings confirm that integrating gamification elements into e-learning can significantly improve students’ motivation and participation in mathematics learning